Bioavailability of Magnesium Salts – A Review - Ragnar Rylander, (Journal of Pharmacy and Nutrition Sciences, 2014)
Background: Magnesium supplementation is of value in several different medical disorders. Several kinds of Mg-salts are commercially available. Purpose: This review evaluates their bioavailability criteria such as solubility, urinary excretion, and plasma levels of magnesium from studies of different Mg-salts. Conclusion: Although methodology differences were large, the results consistently demonstrate a better bioavailability for Mg-citrate.